K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 10 2016

pt vô nghiệm

22 tháng 10 2016

dị đò thôi :))

\(a.x^2-7x-3x+21=0\Leftrightarrow\left(x^2-7x\right)-\left(3x-21\right)=0\)

\(\Leftrightarrow x\left(x-7\right)-3\left(x-7\right)=0\Leftrightarrow\left(x-3\right)\left(x-7\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x-3=0\\x-7=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=7\end{matrix}\right.\)

\(b.x^2+6x+2x+12=0\Leftrightarrow\left(x^2+6x\right)+\left(2x+12\right)=0\)

\(\Leftrightarrow x\left(x+6\right)+2\left(x+6\right)=0\Leftrightarrow\left(x+2\right)\left(x+6\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=-6\end{matrix}\right.\)

\(c.x^2+4x+5x+20=0\Leftrightarrow\left(x^2+4x\right)+\left(5x+20\right)=0\)

\(\Leftrightarrow x\left(x+4\right)+5\left(x+4\right)=0\Leftrightarrow\left(x+5\right)\left(x+4\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=-4\end{matrix}\right.\)

31 tháng 8 2021

\(C=\sqrt{9x^2}-2x=\left|3x\right|-2x=-3x-2x=-5x\left(x< 0\right)\)

\(D=x-4+\sqrt{16-8x+x^2}\left(x>4\right)\)

\(=x-4+\sqrt{\left(x-4\right)^2}\)

\(=x-4+\left|x-4\right|\)

\(=x-4+x-4\)

\(=2x-8\)

31 tháng 8 2021

 

29 tháng 3 2022

a) \(\text{Δ}=8^2-4.3.4=16\)

\(\left[{}\begin{matrix}x=\dfrac{-8+4}{2.3}=-\dfrac{2}{3}\\x=\dfrac{-8-4}{2.3}=-2\end{matrix}\right.\)

29 tháng 3 2022

b) \(\text{Δ}=9^2-4.1.18=9\)

\(\left[{}\begin{matrix}x=\dfrac{-9+3}{2}=-3\\x=\dfrac{-9-3}{2}=-6\end{matrix}\right.\)

\(x^2-8x-9=0\\ x^2+x-9x-9=0\\ x\left(x+1\right)-9\left(x+1\right)=0\\ \left\{{}\begin{matrix}x-3=0\\x+3=0\\x-1=0\end{matrix}\right.\left\{{}\begin{matrix}x=3\\x=-3\\x=1\end{matrix}\right.\)

28 tháng 12 2021

25 tháng 8 2019

a) x = -1.                      b) x = 4 hoặc x = 5.

c) x = ± 2 .                  d) x = 1 hoặc x = 2.

14 tháng 8 2019

18 tháng 4 2017

Ta có 3 x 2 + 8x + 5 = 0

ó 3 x 2 + 3x + 5x + 5 = 0 ó 3x(x + 1) + 5(x + 1) = 0

ó (3x + 5)(x + 1) = 0 

Vậy  x = - 5 3 ;   x = - 1

 

Đáp án cần chọn là: A

10 tháng 3 2020

x3 - 9x2 + 19x - 11 = 0

<=> (x - 1)(x2 - 8x + 11) = 0

<=> x - 1 = 0

<=> x = 1